A review of the effect of hydrogen addition on the performance and emissions of the compression - Ignition engine - Alrazen H.A.; Abu Talib A.R.; Adnan R.; Ahmad K.A. (Elsevier Ltd, 2023)
Air engines; Brakes; Carbon dioxide; Carbon monoxide; Energy utilization; Engines; Exhaust gas recirculation; Hydrogen; Injection (oil wells); Nitrogen; Nitrogen oxides; Oil well flooding; Particulate emissions; Water injection; Brake thermal efficiency; Compression ignition engine; Diesel; Exhaust aftertreatment; Exhaust gas recirculation (EGR); Mechanical configurations; Performance and emissions; Specific energy consumption; Diesel engines